Infant Feeding Practices, Workplace Breastfeeding/Lactation Practices, and Perception of Unit/Service Support Among Primiparous Active Duty Servicewomen. Issue 7 (24th January 2019) - Abbott, Jonathan; Carty, Jenava; Batig, Alison L
Abstract: Introduction: Successful breastfeeding provides multiple health benefits to Servicewomen and their infants and has positive indirect benefits to the military. Workplace lactation support influences breastfeeding continuation after a Servicewoman's return to work. Materials and Methods: This study evaluated the breastfeeding practices and workplace breastfeeding support among primiparous women serving in the U.S. Army. The study was a subanalysis of a non-blinded randomized controlled trial designed to determine the effect of postpartum appointment timing (either 2–3 or 6–8 weeks after delivery) on breastfeeding rates 6 months post-delivery. Subanalysis results were obtained through a telephonic follow-up survey 5–6 months after delivery; Servicewomen were queried to assess their breastfeeding/lactation practices and perception of unit and service support. Results: Eighty of the 97 (82.5%) enrolled Servicewomen participated in the survey. Among respondents, 43.8% were still breastfeeding and 93.6% of those indicated an intent to breastfeed for a duration of 6 months or longer. Among respondents who provided feedback on their workplace, unit, and Army support for breastfeeding/lactation, only 13% reported they had access to a private room, sink, and refrigerator; 53% of respondents felt "mostly" or "very" supported by their assigned unit and 50% felt "mostly" or "very" supported by the Army. Conclusion: While almost half of the respondents were still breastfeeding and planned to continue 5–6 months postpartum and the majority of respondents felt "mostly" or "very" supported in their breastfeeding by their unit and the Army, comprehensive physical support for lactation in the workplace was inconsistent. This study provides feedback to inform ongoing implementation of the existing Army breastfeeding support directive.